The Influence of Organizational Communication Climate Toward Employees Performance - Primadani, Karina Armilia; Alfatih, Andy; Malinda, Febrimarandi (Open Access Indonesia Journal of Social Sciences, 2018)
Advances in technology and information have shaped an increasingly advanced society and make changes every life sector​​. This change has an impact on competition in the business world especially in Indonesia which have many companies. The research design was quantitative descriptive. Research sample was 91 respondents namely employees of PT Pertamina (Persero) RU III Plaju and data collection methods was done by questionnaire and observation. Data analysis began with validation test and questionnaire reliability test, then performed a correlation test and linear regression on the test variable. The results showed an influence of the communication environment of organization for performance of the employees of PT Pertamina (Persero) RU III Plaju was 44.7%.